2022
DOI: 10.1039/d2tc02497g
|View full text |Cite
|
Sign up to set email alerts
|

Bulk heterojunction organic photovoltaic cells based on D–A type BODIPY small molecules as non-fullerene acceptors

Abstract: Two non-fullerene small molecule acceptors based on CF3-4,4-Difluoro-4-bora-3a,4a-diaza-s-indacene (BODIPY) as central acceptor core and different donor terminal triphenylamine and carbazole units denoted as CF3-BDP-1 and CF3-BDP-2, respectively, were designed and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…To support the outcomes obtained from the above-mentioned inspection, the FMO approach is also applied in terms of some electronic parameters such as HOMO, LUMO, their separation ( E LUMO – E HOMO = E gap ), chemical hardness (η), and electronic chemical potential (μ). Such parameters can be seen in Table . The low E gap value infers high global chemical reactivity, as it is energetically favorable to add electrons to a high-lying LUMO to extract electrons from a low-lying HOMO and therefore to form the activated complex of any potential reaction.…”
Section: Resultsmentioning
confidence: 99%
“…To support the outcomes obtained from the above-mentioned inspection, the FMO approach is also applied in terms of some electronic parameters such as HOMO, LUMO, their separation ( E LUMO – E HOMO = E gap ), chemical hardness (η), and electronic chemical potential (μ). Such parameters can be seen in Table . The low E gap value infers high global chemical reactivity, as it is energetically favorable to add electrons to a high-lying LUMO to extract electrons from a low-lying HOMO and therefore to form the activated complex of any potential reaction.…”
Section: Resultsmentioning
confidence: 99%
“…A material shows high electrical conductivity due to having a small E gap value and thus illustrates easy photochemical excitation, which could only be possible because of the unrestricted and competent movement The DFT study using the molecular modelling approach facilitates a lucrative way to gain a high open-circuit voltage of the OSCs, which facilitates the decreased E gap showing a narrow band gap through appropriate molecular surgery in both the probed D-π-A structure alkene groups, which played an imperative role as bridging π-linkers. 61 Therefore, the electronic transport features were obtained from the smaller E gap value permitting the increased tunnelling of photoexcited electrons which also provided a reckonable evaluation of the CT interactions.…”
Section: Quantum Mechanical Calculationsmentioning
confidence: 99%
“…Recently, some novel and efficient electron donor and acceptor materials have been developed based on BODIPY units. 14,[25][26][27][28][29][30] In this case, considering the advantages of the inherent high extinction coefficient of BODIPY as core, the resulting FUEAs are promising to possess strong lightharvest ability. [31][32][33] Moreover, it has been widely reported that weakening molecular coplanarity is beneficial for relieving overstrong aggregation tendency for small-molecule acceptors.…”
Section: Introductionmentioning
confidence: 99%